2017
DOI: 10.1542/peds.2016-4114
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hospitalization Rates for Children With Anaphylaxis

Abstract: We safely reduced unnecessary hospitalizations for children with anaphylaxis and sustained the change over 3 years by using a QI initiative that included evidence-based guideline development and implementation, reinforced by provider reminders and structured feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 19 publications
5
29
0
Order By: Relevance
“…However, 72hour ED revisits for anaphylaxis were rare (2.1%) at our institution during the study period. 20,21 This made it feasible to accrue a large cohort of children who had severe anaphylactic reactions, and it offers a conservative approach for extrapolation to a population of children with less severe symptoms because discharged children likely have less severe reactions. Finally, discharged patients may have visited different EDs after being discharged from our ED, although this was likely uncommon and we would expect these patients to revisit our institution given it is a large referral center.…”
Section: Discussionmentioning
confidence: 99%
“…However, 72hour ED revisits for anaphylaxis were rare (2.1%) at our institution during the study period. 20,21 This made it feasible to accrue a large cohort of children who had severe anaphylactic reactions, and it offers a conservative approach for extrapolation to a population of children with less severe symptoms because discharged children likely have less severe reactions. Finally, discharged patients may have visited different EDs after being discharged from our ED, although this was likely uncommon and we would expect these patients to revisit our institution given it is a large referral center.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in a tertiary care pediatric institution and limited to hospitalized children which may limit the generalizability of our findings. It should be noted that our hospitalization and ICU admission rates for patients with anaphylaxis are similar to other U.S. children’s hospitals [13,14]. We studied hospitalized children because our goal was to reduce unnecessary hospitalizations; however, we were unable to assess whether children discharged from the ED received acute therapies such as epinephrine after discharge.…”
Section: Discussionmentioning
confidence: 93%
“…The study was conducted at an urban, tertiary care children’s hospital with an annual ED volume of approximately 60,000 visits. During the study period the hospitalization rate for patients presenting to the ED with anaphylaxis was 44% [14]. Children with anaphylaxis at our institution are typically observed for 4 hours prior to ED discharge and are hospitalized if they have cardiac involvement or receive 2 or more doses of IM epinephrine in the prehospital or ED settings.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we evaluated how our system prioritized children attended for anaphylaxis in the PEU, noting that 66% were underprioritized and thus experienced delays in receiving their treatment [10]. Other authors have reported similar results [11].…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, allergists may and should help to analyze the allergies category in current triage systems jointly with ED specialists. With respect to training, Farbman et al [11] showed how educational measures reduced anaphylaxis-related admission rates. Our results show that carrying out training activities aimed at triage staff and introducing adjustments in the triage system to take account of the peculiarities of anaphylaxis improved identification of patients and dramatically reduced waiting times for medical attention.…”
Section: Discussionmentioning
confidence: 99%